Adsorption of pollutants from liquid swine manure through the application of metabasalt rock powder (2022)
Adequate animal manure disposal became a challenge in agriculture. Liquid swine waste (LSW), easily used in agriculture, presents disadvantages due to the high volume and low nutrient concentrations. Metabasalt powder, a residue of amethyst mining, was evaluated as an adsorbent agent of nutrients (Cu, Zn, P, and K) from LSW. Seven doses of metabasalt powder were tested in proportion with LSW (0, 4, 10, 20, 40, 80, and 160 kg m−3), and during four contact times (CT) (9, 21, 42, and 84 days) and ions were dosed in the liquid and solid fractions. Copper and phosphorus concentrations in the liquid fraction were lower at 21 days of contact. The lowest concentration of zinc in the liquid fraction was observed at the dose of 10 kg m−3 of metabasalt powder, and at 9 days of CT. The K concentrations in the liquid fraction diminished linearly with the metabasalt doses, in which the major dose presented 51% of K compared to the control. The application of metabasalt as an adsorbent agent reduced the contaminant charge in the liquid fraction of LSW, suggesting safe water disposal while promoting ion accumulation in the solid fraction. The use of metabasalt powder became a useful strategy to make LSW pre-treatment on-farm.